2022
DOI: 10.1002/ana.26514
|View full text |Cite
|
Sign up to set email alerts
|

Regional Precuneus Cortical Hyperexcitability in Alzheimer's Disease Patients

Abstract: Objective Neuronal excitation/inhibition (E/I) imbalance is a potential cause of neuronal network malfunctioning in Alzheimer's disease (AD), contributing to cognitive dysfunction. Here, we used a novel approach combining transcranial magnetic stimulation (TMS) and electroencephalography (EEG) to probe cortical excitability in different brain areas known to be directly involved in AD pathology. Methods We performed TMS‐EEG recordings targeting the left dorsolateral prefrontal cortex (l‐DLPFC), the left posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In recent years, novel neurophysiological techniques, such as transcranial magnetic stimulation (TMS), have been investigated in neurodegenerative diseases to better characterise some aspects of cortical circuitry, plasticity, reactivity, and connectivity [228,229]. Undoubtedly, the most investigated pathology has been AD, in which several correlations with neuropsychological and neuropathological biomarkers have been made, showing that AD is characterised by an impairment of cortical plasticity, hyperexcitability, and altered connectivity [230], mirroring the neuropathological studies in animal models [231].…”
Section: Neurophysiologymentioning
confidence: 99%
“…In recent years, novel neurophysiological techniques, such as transcranial magnetic stimulation (TMS), have been investigated in neurodegenerative diseases to better characterise some aspects of cortical circuitry, plasticity, reactivity, and connectivity [228,229]. Undoubtedly, the most investigated pathology has been AD, in which several correlations with neuropsychological and neuropathological biomarkers have been made, showing that AD is characterised by an impairment of cortical plasticity, hyperexcitability, and altered connectivity [230], mirroring the neuropathological studies in animal models [231].…”
Section: Neurophysiologymentioning
confidence: 99%
“…TMS stimulation led to pronounced excitability in the DLPFC [73], a crucial element in cortical plasticity and cognitive function [74]. The findings suggest that rTMS holds promise as an efficacious intervention for AD by augmenting cortical excitability [19,[75][76][77] and enduring neuroplasticity alterations [51,78,79]. Furthermore, some studies indicated that post-TMS treatment, neural activity in the anterior cingulate cortex was enhanced, brain oscillations in the beta band intensified, and functional connections between the anterior cingulate cortex and medial frontal lobe region of the default mode network (DMN) were transformed [80].…”
Section: Discussionmentioning
confidence: 96%
“…Tau protein accumulation is known to promote network hyperexcitability and in an AD murine model its reduction resulted in a decreased hyperexcitability, independently from the presence of Aβ42 (Tok, Ahnaou, and Drinkenburg 2022). Moreover, a recent study in AD patients found a positive linear correlation between the amplitude of the TMS-evoked potential (TEP) at the level of the posterior parietal cortex and the levels of tau and p-tau in CSF (Casula et al 2022). Hence, we hypothesize that the presence of tau protein and neurodegeneration could locally disrupt of the physiological rhythms, forcing the remaining neurons to increase their activity, to maintain the excitatory/inhibitory balance.…”
Section: Discussionmentioning
confidence: 99%